Northwest History. Alaska. Earthquakes & Volcanoes. (1937)
Earthquake Jars Big Area In Interior Country. EARTHQUAKE JARS BIG AREA IN INTERIOR COUNTRY BLACK RAPIDS GLACIER STARTS ON RAMPAGE AS RESULT SHAKE FAIRBANKS, Alaska, —The earthquakes which rocked east, centraj and other parts of Alaska Thursday morning, left damage to the extent of $5,000 in broken windows and bottled goods. Numerouus slides were reported from the JRichardson highway, one of which was said to be 2,000 feet long. The Black Rapids glacier, southwest of here, which for a time last winter was moving down the valley at the unprecedented rate of two miles a month, was reported jarred into renewed activity by the series of tremors. One death, unconfirmed, was reported along the Richardson highway which may be closed to traffic for a considerable period. A number of auto travelers, heading for the coast, returned to Fairbanks and routed over the Alaska Railroad for Seward.